Forty years of irrigation development and reform in China. (11th September 2019) - Wang, Jinxia; Zhu, Yunyun; Sun, Tianhe; Huang, Jikun; Zhang, Lijuan; Guan, Baozhu; Huang, Qiuqiong
Abstract : This study reviews 40 years of irrigation development in China including the transformation of the institutional and incentive structures in irrigation management. After rural reforms in the 1970s, irrigation investments slowed until the late 1990s. In North China, farmers became major investors in groundwater irrigation, leading to property rights' transfer of tube wells from collective to private ownership. Despite positive effects in cropping patterns, farmer income and development of groundwater markets, privatisation has accelerated groundwater table deterioration. Since the middle of 1990s, Water User Associations have replaced village collective management of surface irrigation. This approach was adopted by most provinces by early 2001 with mixed results; only institutions with water‐saving incentives realised efficient irrigation. The Government is reforming water price policies to provide water‐saving incentives to farmers while not hurting their income. While China has focused on water rights and markets, and despite regulations and pilot projects, full implementation of water rights has been slow. Research reveals greater policy scope for expanding irrigation technologies that generate real water saving to rural areas. Given pressure associated with water scarcity and concern for food security, further effective reforms in irrigation and policy incentives are expected. The Government has also initiated some pilot projects to resolve increasing water scarcity problems through adjusting agricultural production activities.